Symptom-related experience and sexual health of female patients with pulmonary arterial hypertension: protocol for a systematic review and qualitative meta-synthesis - Ye He; Zhu Yang; Lixiao Yang; Fangfang Ma (BMJ Open)
Introduction Pulmonary arterial hypertension (PAH) is a complex condition affecting quality of life, characterised by high blood pressure in the pulmonary arteries leading to heart strain. PAH’s impact extends beyond physical symptoms, influencing emotional and social well-being, particularly in women where it affects sexual health and pregnancy outcomes. Despite medical advancements, the disease’s full impact on women’s lives is under-researched, especially regarding sexual experiences and health. This systematic review and qualitative meta-synthesis aim to address this gap by examining women’s experiences with PAH, informing clinical practice and patient-centred care. The protocol outlines a methodology for synthesising qualitative research to amplify women’s voices and enhance our understanding of PAH’s impact on female patients.Methods and analysis Search strategy: A systematic review and thematic meta-synthesis of qualitative research studies and qualitative components of mixed-methods studies will be conducted. The systematic review will be guided by the Joanna Briggs Institute methodological framework. A comprehensive search will encompass seven electronic databases and search engines (Ovid Medline, CINAHL, EMBASE, APA PsycINFO, Cochrane Database of Systematic Reviews, PubMed, Scopus) and grey literature sources (ProQuest Dissertations, ClinicalTrials.gov). Building on insights from previous reviews centred on symptom-related experience and sexual health. Two review authors will independently conduct the screening and data extraction processes. Discrepancies will be resolved through consensus or discussion with a third review author. The review will include English studies from database inception. Findings will be presented graphically and tabularly, together with a narrative description.Assessment of confidence and data synthesis: The meta-synthesis used thematic analysis, importing study transcripts and notes into NVivo software. Data-derived codes formed categories, which were then iteratively refined into broader themes reflecting women’s experiences with sex and childbirth while living with PAH.Ethics and dissemination External ethical approval is not required as this review is a retrospective review, which is undertaking secondary analysis of publicly available primary data. The results will be disseminated in peer-reviewed journals and presented in conference papers and elsewhere. This protocol is registered with PROSPERO prospective database of systematic review.PROSPERO registration number CRD42024529342.